2009
DOI: 10.1021/ol900778m
|View full text |Cite
|
Sign up to set email alerts
|

Cp2Ni-KOt-Bu-BEt3 (or PPh3) Catalyst System for Direct C−H Arylation of Benzene, Naphthalene, and Pyridine

Abstract: Ni-catalyzed direct C-H arylation of benzene and naphthalene using aryl halides was investigated. For the first time, the arylation was successfully catalyzed by Cp(2)Ni (5 mol %) in the presence of KOt-Bu and BEt(3). This Ni catalyst system was also applied to direct C-H arylation of pyridine, an electron-deficient heteroarene; PPh(3) was used instead of BEt(3) in this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 40 publications
2
65
0
1
Order By: Relevance
“…[170] Li and Hua found that mixtures of 2-, 3-and 4-arylpyridines were also efficiently obtained by the reaction of a large molar excess of pyridine (242) aryl bromides in the presence of t-BuOK using Cy 3 PAuCl (5 mol%) as the catalyst.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…[170] Li and Hua found that mixtures of 2-, 3-and 4-arylpyridines were also efficiently obtained by the reaction of a large molar excess of pyridine (242) aryl bromides in the presence of t-BuOK using Cy 3 PAuCl (5 mol%) as the catalyst.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…[26] The transition metal-mediated radical C À H arylation of (hetero)arenes has the advantage of requiring only a catalytic amount of radical initiator, but it usually requires several equivalents of a strong base and a very large excess of (hetero)arene. Iridium, [27] cobalt, [28] nickel [29] and iron [30] catalysts have been used to carry out the direct C À H arylation of unactivated arenes with good to excellent yields, starting from aryl iodides, bromides and even chlorides, although with lower yields in the latter case. [29] Li and Hua described the first transition metalmediated radical arylation of electron-poor pyridine using an Au(I) catalyst.…”
Section: Aromatic Halidesmentioning
confidence: 99%
“…Iridium, [27] cobalt, [28] nickel [29] and iron [30] catalysts have been used to carry out the direct C À H arylation of unactivated arenes with good to excellent yields, starting from aryl iodides, bromides and even chlorides, although with lower yields in the latter case. [29] Li and Hua described the first transition metalmediated radical arylation of electron-poor pyridine using an Au(I) catalyst. [31] The reaction was examined with pyrazine as well, but mechanistic investigations using 1,2-dihydroxybenzene as radical inhibitor showed that a radical pathway was probably not involved with this substrate.…”
Section: Aromatic Halidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] Various transition metals have been reported as efficient catalysts for this transformation, for example, Pd, [4][5][6][7][8][9][10][11] Rh, [12][13][14][15] Ru, [16][17][18] Ir, [19,20] Cu, [21][22][23][24][25][26][27] and other transition metals. [28][29][30] The application of inexpensive, non-toxic, commercially available, and environmentally benign iron complexes as catalysts in chemical syntheses has attracted much attention. [31,32] Recently, iron has been utilized extensively as a catalyst to promote the "traditional" cross-coupling between R 1 X and R 2 M. [33][34][35][36][37][38][39][40][41] Iron catalysts are also involved in many important transformations, such as Friedel-Crafts benzylation, [42,43] carbonylation, [44] oxidation [45,46] and other processes.…”
mentioning
confidence: 99%